Evaluating Effectiveness of Spiritual Health Education on Increasing Hope among Breast Cancer Patients - Shaghayegh Kamian; Mohammad Hossein Taghdisi; Kamal Azam; Fatemeh Estebsari; soheila ranjbaran; afsaneh geravand (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: The cancer diagnosis endangers spiritual health, and ultimately results in losing hope in the person. This study aimed to evaluate effectiveness of training based on promoting spiritual health on the level of hope in patients with breast cancer referred to Imam Hossein Hospital in Tehran. Method: This was a quasi-experimental study performed as a controlled intervention. In this study, 100 women suffered from breast cancer who were referred to Imam Hossein Hospital in Tehran were selected in 2013, then randomly allocated to two intervention and control groups (each group=50 people). The standardized questionnaire of spiritual health by Palotzian and Elison, and the hope questionnaire by Herth were completed before and one month after the intervention in both intervention and control groups. Data was analyzed statistical tests such as chi-square, independent and paired T test, Pearson correlation coefficient. Results: The mean score of spiritual health and The mean score of hope were significantly higher in the intervention group than the control group (p<0.001). Significant correlation between the mean scores for the spiritual health and hope was found (p<0.001). Conclusion: The training intervention based on promoting spiritual health was effective in increasing the level of hope in patients. Considering the key role of spirituality and revival of spiritual health in return of these patients to normal life, it is necessary to adopt special attention by health officials to this issue. Paper Type: Research Article